2023
DOI: 10.1093/fqsafe/fyad016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novelBacillus methylotrophicusphage BM-P1

Abstract: Bacillus species have been widely used as probiotics in a number of food products. However, these are vulnerable to bacteriophage infections which poses fermentation failure and eventually result in economic losses. Given this, we designed this study in which bacteriophage of lysogenic Bacillus methylotrophicus, Phage BM-P, was induced successfully, and its biological characteristics and genome information were researched. The obtained results showed that Bacillus species phage belonged to Myoviridae family. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Similar to our results, Quiberoni reported that Ca 2+ had no effect on the adsorption kinetics of phage BYM and phage LL-H [41]. Briggiler Marcó et al found that regardless of whether calcium ions were added, the adsorption rate of phages would reach 99% at 15 min [14]. In 2016, Chen et al reported that divalent cations were not necessary for the adsorption of L. plantarum phage P1 but could accelerate the lytic process [46].…”
Section: Influence Of Divalent Cations On Phage Adsorptionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to our results, Quiberoni reported that Ca 2+ had no effect on the adsorption kinetics of phage BYM and phage LL-H [41]. Briggiler Marcó et al found that regardless of whether calcium ions were added, the adsorption rate of phages would reach 99% at 15 min [14]. In 2016, Chen et al reported that divalent cations were not necessary for the adsorption of L. plantarum phage P1 but could accelerate the lytic process [46].…”
Section: Influence Of Divalent Cations On Phage Adsorptionsupporting
confidence: 89%
“…Müller-Merbach et al found that Lactococcus lactis phage P008 reduced only 1 log 10 at 55 • C for 3 h [32]. Briggiler Marcó et al also found that the survival of L. plantarum bacteriophages (B1, B2, FAGK1, and FAGK2) was 95% after incubation at 50 • C for 30 min [14]. Therefore, compared to other Lactobacillus phages, phage LFP02 is more sensitive to temperature.…”
Section: Thermal Stabilitymentioning
confidence: 99%
See 2 more Smart Citations